2022
DOI: 10.3390/v14061295
|View full text |Cite
|
Sign up to set email alerts
|

Borneol Ester Derivatives as Entry Inhibitors of a Wide Spectrum of SARS-CoV-2 Viruses

Abstract: In the present work we studied the antiviral activity of the home library of monoterpenoid derivatives using the pseudoviral systems of our development, which have glycoproteins of the SARS-CoV-2 virus strains Wuhan and Delta on their surface. We found that borneol derivatives with a tertiary nitrogen atom can exhibit activity at the early stages of viral replication. In order to search for potential binding sites of ligands with glycoprotein, we carried out additional biological tests to study the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…To find out whether the usnic acid derivatives are virus entry inhibitors, additionally synthesized compounds were tested in a neutralization assay using pseudoviruses bearing S glycoprotein S of the SARS-CoV-2 virus on their surface. In this study, HEK293T-hAce2-TMPRSS2 (transient) cell lines were used according to the methodology described in [ 56 ]. We used Arbidol as a reference drug.…”
Section: Resultsmentioning
confidence: 99%
“…To find out whether the usnic acid derivatives are virus entry inhibitors, additionally synthesized compounds were tested in a neutralization assay using pseudoviruses bearing S glycoprotein S of the SARS-CoV-2 virus on their surface. In this study, HEK293T-hAce2-TMPRSS2 (transient) cell lines were used according to the methodology described in [ 56 ]. We used Arbidol as a reference drug.…”
Section: Resultsmentioning
confidence: 99%
“…Many different classes of camphor-based derivatives have been synthesized with a wide range of antiviral properties. We have previously shown that derivatives with a 1,7,7-trimethylbicyclo[2.2.1]heptane backbone exhibit a wide spectrum of antiviral activity against influenza [ 7 , 8 ], hantaviruses [ 9 ], filoviruses [ 10 , 11 , 12 ], orthopoxviruses [ 13 , 14 ] and SARS-CoV-2 [ 15 ]. Some compounds, with a heterocyclic fragment synthesized previously on the basis of camphor and borneol, which have shown significant antiviral properties, are presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…9 The signifi cant library of the ester derivatives based on natural alcohol (-)-borneol containing N-heterocyclic fragments is characterized by a broad range of antiviral activity: the compounds are active against infl uenza viruses, 10 Ebola virus, 11 Marburg virus, 12 respiratory syncytial virus, 13 and Orthopoxviruses, 14 including smallpox virus, 15 and are entry inhibitors of the SARS-CoV-2 virus. 16 Ethers bearing bicyclobornane framework and N-heterocyclic fragments also have a wide range of antiviral activity. 17 (1R,3S)-(+)-Camphoric acid ( 1) is an available commercial compound and can be synthesized by the exhaustive oxidation of natural (+)-camphor.…”
mentioning
confidence: 99%
“…)), 21.4 (C(7)), 22.2 (C(8)), 27.5 (C(4)), 34.5 (C(5)), 47.1 (C(2)), 52.1, 52.8, 52.9, 53.2, 53.3 (C(13), С(14), С(15), С(16), С(17), С(18), С(19), С(20)); 54.7 (С(3)), 61.4 (С(12)), 62.0 (С(11)), 62.5 (С(1)), 169.2 and 169.7 (С(9), С(10)). HR MS: found m/z 450.3680 [M] + ; calculated for C 24 H 46 N 6 (4j).…”
mentioning
confidence: 99%
See 1 more Smart Citation